2002
DOI: 10.1021/np020059e
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic 3,20-Epoxy-ent-Kaurane Diterpenoids from Isodon eriocalyx var. laxiflora

Abstract: Four new ent-kaurane diterpenoids, laxiflorins J-M (1-4), along with maoecrystal A (5) and maoecrystal P (6), were isolated from the leaves of Isodon eriocalyx var. laxiflora. Their structures were determined by spectroscopic analyses. All the compounds were assayed for their cytotoxic effects on human tumor K562, A549, and T24 cell lines. Compounds 1 and 6 showed significant inhibitory effects on human tumor K562 and T24 cells, with IC(50) values less than 0.5 microg/mL. Compound 3 also demonstrated cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…This difference was supported by HMBC correlations from H-15 (δ H 6.40, s) and The ROESY cross peaks correlations indicated that compounds 2 and 7 had the same relative configuration. Consequently, compound 2 was 7β,13α-dihydroxy-6β,15β-diacetoxy-7,20-epoxy-ent-kaur-16-en-1-one, and it was named laxiflorin T. (Tables 1 and 2) indicated that it was structurally very similar to neolaxiflorin D (8). 12 The most notable difference was that the C-13 carbonyl group in compound 8 (δ C 208.7, s) 12 changed into hydroxy group in compound 3 (δ C 63.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference was supported by HMBC correlations from H-15 (δ H 6.40, s) and The ROESY cross peaks correlations indicated that compounds 2 and 7 had the same relative configuration. Consequently, compound 2 was 7β,13α-dihydroxy-6β,15β-diacetoxy-7,20-epoxy-ent-kaur-16-en-1-one, and it was named laxiflorin T. (Tables 1 and 2) indicated that it was structurally very similar to neolaxiflorin D (8). 12 The most notable difference was that the C-13 carbonyl group in compound 8 (δ C 208.7, s) 12 changed into hydroxy group in compound 3 (δ C 63.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 As one of the important plants of Isodon genus, I. eriocalyx var. laxiflora has been investigated phytochemically as it is a rich source of diterpenoids, such as 7,20-epoxy-ent-kauranoids (laxiflorins H and I), 6 3,20-epoxy-ent-kauranoids (laxiflorins J-M), 7,8 6,7-seco-ent-kauranoids (laxiflorins A-C), 9 6,7:8,15-seco-ent-kauranoids (laxiflorins F and G), 10 ent-abietanoids (laxiflorin N), 11 15,16-seco-16,17-dinor-ent-kauranoids (neolaxiflorins D-F) 12 , two unprecedented epimeric bishomoditerpene lactones with a unique C 22 framework (laxiflorolides A and B), 13 and two unprecedented ent-kaurane diterpenoids (neolaxiflorins A and B).…”
Section: Introductionmentioning
confidence: 99%
“…Tetracyclic diterpenoids with hydrocarbon skeletons derived from a rearranged norkaurane-type structure are widespread among the plant metabolites (Bruno et al, 2002;Niu et al, 2002;Hanson, 2003, and references therein). Many of these substances exhibit biological activities that are well known from ancient times and are used by traditional healers in the treatment of various diseases.…”
Section: Commentmentioning
confidence: 99%
“…), a natural product first isolated in 2002 by our group from the leaves of Isodon eriocalyx var . laxiflora C. Y. Wu & H. W. Li shows significant inhibitory activity toward T‐24 cells .…”
Section: Introductionmentioning
confidence: 99%